Eurocities as “Collaboration Laboratories”: Innovation and Policy Development within the European Union - Carla Valadas (População e Sociedade)
The evolving political and social space constituting the EU has increasingly impacted member states’ domestic policies and polities, while also regulating the daily lives of individuals. This has been achieved, notably, by bringing non-governmental actors into the policy-making process. The principle that various actors are involved in the implementation of EU policy is crucial for the multi-level governance system to function effectively. The main purpose of this article is to shed light on the complex interrelations within border territories and how Europeanisation processes are shaped by specific circumstances and regions. Focusing on a case study – the WaterEurocity – an initial assessment suggests that cooperation among local stakeholders can lead to innovative approaches for developing social, cultural, and economic frameworks. Such collaborations have the potential to build stronger, more unified communities and pave the way for novel methods of experiencing and promoting European integration.